The Polemics of Mauquf 'Alaih in Cash Waqf and Waqf through Cash: Perspectives from Shafi'i Fiqh and the Waqf Law - Tengku Muhammad Laksamana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The practice of cash waqf and waqf through money in Indonesia still faces problems, particularly concerning the protection of the rights of the mauquf 'alaih (beneficiaries) and the condition of perpetuity of the assets. This research aims to analyze the position and requirements of the mauquf 'alaih in these waqf schemes, as well as the legal implications if there is a deviation in management. The method used is qualitative research with a normative approach through a literature study of the Shafi'i school of thought (fiqh) literature and Law Number 41 of 2004. The research results show that: (1) there is a difference of legal status between classical Shafi'i fiqh which rejects cash waqf and Indonesian regulations that legalize it (2) the weak competence of nazhir which has the potential to eliminate the waqf status and harm the rights of the mauquf 'alaih (3) legal protection mechanisms through LKS-PWU and BWI supervision are not yet optimal and weak enforcement of sanctions. This research emphasizes the necessity of socializing cash waqf and waqf through money to the community, strengthening the competence of nazhir, and implementing mechanisms to protect the rights of mauquf 'alaih from the risk of investment losses or depreciation of productive waqf assets.